Influencing the global forest policy agenda: an evaluation of CIFOR's research - Spilsbury, M.J.; Bose, P. (Center for International Forestry Research, 2005)
Center for International Forestry Research (CIFOR) research projects attempt to achieve impact by promoting the uptake of research findings across differing ‘impact pathways’. Some CIFOR research outputs are tailored to specific local situations, however many more research outputs are intended to be of international relevance and are often widely disseminated. This paper summarises literature on the influence of research on policy, highlights key organizations that act to shape the international forest agenda and explores the nature and significance of citations, and other bibliographic information as evidence of research influence on policy. Two broad, and partially overlapping, policy impact pathways are examined: 1.) research influence on organizations responsible for major financial flows to forest-related development assistance; 2.) research influence on the key organizations that help shape the global forest agenda. Evidence of CIFOR influence on important international policy actors and policy processes is drawn from bibliographic analysis (citations, acknowledgements and author contributions) in the 309 important forest-related policy documents examined. The findings highlight the success CIFOR has achieved in shaping the views and actions of influential organizations and actors at the international level including the World Bank, FAO and the CBD.